Ring-opening metathesis of some strained bicyclic systems; stereocontrolled access to diolefinated saturated heterocycles with multiple stereogenic centers - Benke, Zsanett; Nonn, Melinda; Kardos, Márton; Fustero, Santos; Kiss, Loránd (Beilstein Journal of Organic Chemistry, 2018)
Ring-opening metathesis (ROM) of various unsaturated, constrained bicyclic ring systems has been investigated with the use of commercial ruthenium-based catalysts. Starting from various cyclodienes, the corresponding derived bicyclic lactone, lactam, and isoxazoline derivatives were submitted to ROM under ethenolysis. These functionalized, strained bicyclic systems afforded novel highly-functionalized diolefinated heterocyclic scaffolds in ROM reactions with stereocontrol, through the conservation of the configuration of the stereogenic centers of the starting compounds.
Keywords: functionalization; heterocycles; metathesis; ring opening; stereogenic centers

(untitled) - Hoveyda, A. H.; Zhugralin, A. R. (Nature, 2007)

(untitled) - Bidange, J.; Fischmeister, C.; Bruneau, C. (Chem. – Eur. J., 2016)

(untitled) - Trnka, T. M.; Grubbs, R. H. (Acc. Chem. Res., 2001)

(untitled) - Sánchez-Roselló, M.; Miró, J.; del Pozo, C. (Synthesis, 2017)

(untitled) - Meek, S. J.; O’Brien, R. V.; Llaveria, J.; Schrock, R. R.; Hoveyda, A. H. (Nature, 2011)

(untitled) - Fustero, S.; Simón-Fuentes, A.; Barrio, P.; Haufe, G. (Chem. Rev., 2015)

(untitled) - Kress, S.; Blechert, S. (Chem. Soc. Rev., 2012)

(untitled) - Higman, C. S.; Lummiss, J. A. M.; Fogg, D. E. (Angew. Chem., Int. Ed., 2016)

(untitled) - Prunet, J. (Eur. J. Org. Chem., 2011)

(untitled) - Hughes, D. L. (Org. Process Res. Dev., 2016)

(untitled) - Garcia-Castro, M.; Zimmermann, S.; Sankar, M. G.; Kumar, K. (Angew. Chem., Int. Ed., 2016)

(untitled) - Hung, A. W.; Ramek, A.; Wang, Y.; Kaya, T.; Wilson, J. A.; Clemons, P. A.; Young, D. W. (Proc. Natl. Acad. Sci. U. S. A., 2011)

(untitled) - Foley, D. J.; Doveston, R. G.; Churcher, I.; Nelson, A.; Marsden, S. P. (Chem. Commun., 2015)

(untitled) - Kiss, L.; Kardos, M.; Forró, E.; Fülöp, F. (Eur. J. Org. Chem., 2015)

(untitled) - Kardos, M.; Kiss, L.; Fülöp, F. (Asian J. Org. Chem., 2015)

(untitled) - Kardos, M.; Kiss, L.; Haukka, M.; Fustero, S.; Fülöp, F. (Eur. J. Org. Chem., 2017)

(untitled) - Spandl, R. J.; Díaz-Gavilán, M.; O’Connel, K. M. G.; Thomas, G. L.; Spring, D. R. (Chem. Rec., 2008)

(untitled) - O’ Connor, C. J.; Beckmann, H. S. G.; Spring, D. R. (Chem. Soc. Rev., 2012)

(untitled) - Sen, S.; Prabhu, G.; Bathula, C.; Hati, S. (Synthesis, 2014)

(untitled) - Collins, S.; Bartlett, S.; Nie, F.; Sore, H. F.; Spring, D. R. (Synthesis, 2016)

(untitled) - Kiss, L.; Fülöp, F. (Chem. Rev., 2014)

(untitled) - Kiss, L.; Mándity, I. M.; Fülöp, F. (Amino Acids, 2017)

(untitled) - Kiss, L.; Fülöp, F. (Chem. Rec., 2018)

(untitled) - Singh, R.; Vince, R. (Chem. Rev., 2012)

(untitled) - Kiss, L.; Forró, E.; Fustero, S.; Fülöp, F. (Eur. J. Org. Chem., 2011)

(untitled) - Kiss, L.; Forró, E.; Fustero, S.; Fülöp, F. (Org. Biomol. Chem., 2011)

Handbook of Metathesis - Grubbs, R. H.; Khosravi, E. (2004)

(untitled) - Ofstead, E. A.; Calderon, N. (Makromol. Chem., 1972)

(untitled) - Tuba, R.; Balogh, J.; Hlil, A.; Barłóg, M.; Al-Hashimi, M.; Bazzi, H. S. (ACS Sustainable Chem. Eng., 2016)

(untitled) - Palkó, M.; Benedek, G.; Forró, F.; Wéber, E.; Hänninen, M.; Sillanpää, R.; Fülöp, F. (Tetrahedron: Asymmetry, 2010)

(untitled) - Arjona, O.; Csáky, A. G.; León, V.; Medel, R.; Plumet, J. (Tetrahedron Lett., 2004)

(untitled) - Arjona, O.; Cabas, M. J.; Nieto-Rubio, J.; Querejeta, A. (Heterocycles, 2006)

(untitled) - Ogba, O. M.; Warner, N. C.; O’Leary, D. J.; Grubbs, R. H. (Chem. Soc. Rev., 2018)

(untitled) - Chatterjee, A. K.; Choi, T.-L.; Sanders, D. P.; Grubbs, R. H. (J. Am. Chem. Soc., 2003)

Olefin metathesis; Theory and practice - Grela, K. (John Wiley & Sons, Inc., 2014)

(untitled) - Kotha, S.; Dipak, M. K. (Tetrahedron, 2012)

(untitled) - Hamad, F. B.; Sun, T.; Xiao, S.; Verpoort, F. (Coord. Chem. Rev., 2013)